2010
DOI: 10.1073/pnas.0912030107
|View full text |Cite
|
Sign up to set email alerts
|

Guard cell anion channel SLAC1 is regulated by CDPK protein kinases with distinct Ca 2+ affinities

Abstract: In response to drought stress, the phytohormone abscisic acid (ABA) induces stomatal closure. Thereby the stress hormone activates guard cell anion channels in a calcium-dependent, as well as -independent, manner. Open stomata 1 protein kinase (OST1) and ABI1 protein phosphatase (ABA insensitive 1) represent key components of calcium-independent ABA signaling. Recently, the guard cell anion channel SLAC1 was identified. When expressed heterologously SLAC1 remained electrically silent. Upon coexpression with Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
573
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(605 citation statements)
references
References 53 publications
26
573
1
5
Order By: Relevance
“…Further research on the structural basis for the HT1-OST1 interaction and phosphorylation sites on OST1 will provide a more detailed molecular mechanism underlying OST1 inhibition by HT1 kinase. Given SLAC1 is also regulated by other protein kinases including CPKs [30][31][32] and calcium sensor kinases CBL-CIPKs 52 , further work should also be conducted to find out whether HT1, similar to the PP2C A-type phosphatases in ABA signalling, can also interact with and inhibit calcium-dependent kinases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research on the structural basis for the HT1-OST1 interaction and phosphorylation sites on OST1 will provide a more detailed molecular mechanism underlying OST1 inhibition by HT1 kinase. Given SLAC1 is also regulated by other protein kinases including CPKs [30][31][32] and calcium sensor kinases CBL-CIPKs 52 , further work should also be conducted to find out whether HT1, similar to the PP2C A-type phosphatases in ABA signalling, can also interact with and inhibit calcium-dependent kinases.…”
Section: Discussionmentioning
confidence: 99%
“…A group of kinases such as OST1 (STOMATAL OPEN 1), CPKs (Ca 2 þ -dependent protein kinases) and GHR1 (GUARD CELL HYDROGEN PEROXIDE-RESISTANT 1) can phosphorylate and activate the SLAC1 anion channel 23,24,[29][30][31][32] . Such activation is often considered to be the key step for ABA-induced stomatal closure [21][22][23][24] .…”
mentioning
confidence: 99%
“…The phenotype of single gene mutants in the key SnRK2 for stomatal responses to ABA, OST1, are profound, displaying no sensitivity to ABA (Mustilli et al, 2002) or VPD (Merilo et al, 2013;Merilo et al, 2015). While other SnRK2-independent signaling pathways for ABA perception and SLAC activation have been suggested (Geiger et al, 2010;Brandt et al, 2012;Pornsiriwong et al, 2017), these are redundant and many either converge or require cross-talk with functional OST1 to activate anion channels (Brandt et al, 2015). Whether these alternative SnRK2-independent ABA signaling pathways play an adaptively relevant role in stomatal function is yet to be determined.…”
Section: Co-option Of An Ancient and Highly Conserved Aba Signaling Pmentioning
confidence: 99%
“…Structural analysis revealed that the interaction between SnRK2.6 and HAB1 mimics the interaction between ABA-bound PYL2 and HAB1 [12]. PYLs can inhibit PP2C activity in the presence of ABA, and thereby activating SnRK2.6, which can phosphorylate slow anion channel1 (SLAC1) and activate SLAC1-mediated ion currents [13,14].…”
Section: Introductionmentioning
confidence: 99%